Plantar pressure modifications in experienced runners following an exhaustive run. Issue 10 (26th November 2022) - Bercovitz, Tomer; Herman, Amir; Solomonow-Avnon, Deborah; Wolf, Alon; Kodesh, Einat
ABSTRACT: Running-induced fatigue alters foot strike pattern. The purpose of this study was to assess plantar pressure and centre of pressure (CoP) trajectory alterations after a 30-minute run at sub-maximal speed in experienced long-distance runners. Plantar pressure data from 9 experienced heel-to-toe male runners was collected before and after a 30-minute run on a treadmill at a speed 5% above the respiratory compensation point (RCP) of each participant. Significant changes in the plantar-pressure map were found post-run, including increased impulses in the first metatarsal head (9.92%, p < 0.001) and hallux areas (16.19%, p < 0.001), and decreased impulses in the fourth and fifth metatarsal heads (4.95%, p < 0.05). The CoP curve showed a medial shift ( p < 0.01). The plantar-pressure map and CoP trajectory were altered following a 30-minute exhausting run. These changes may indicate an increase in stress on joints and tissues when individuals are fatigued and may promote overload injuries.